2011
DOI: 10.1302/0301-620x.93b10.27078
|View full text |Cite
|
Sign up to set email alerts
|

The burden of arthroscopy of the knee

Abstract: Arthroscopy of the knee is one of the most commonly performed orthopaedic procedures worldwide. Large-volume outcome data have not previously been available for English NHS patients. Prospectively collected admissions data, routinely collected on every English NHS patient, were analysed to determine the rates of complications within 30 days (including re-operation and re-admission), 90-day symptomatic venous thromboembolism and all-cause mortality. There were 301,701 operations performed between 2005 and 2010-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 20 publications
3
31
0
1
Order By: Relevance
“…With an estimated incidence of 10 knee arthroscopic procedures per 10,000 population performed in the National Health Service (NHS) in England annually, there is clearly a need to consider the evidence for improved teaching modality for this specific skill set [ 17 ]. Two recent systematic reviews demonstrated a high level of internal consistency and validity using simulators for arthroscopy skills training.…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated incidence of 10 knee arthroscopic procedures per 10,000 population performed in the National Health Service (NHS) in England annually, there is clearly a need to consider the evidence for improved teaching modality for this specific skill set [ 17 ]. Two recent systematic reviews demonstrated a high level of internal consistency and validity using simulators for arthroscopy skills training.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the information regarding complications after knee arthroscopy dates back to the 1980s, with rates ranging between 0.6 and 8.2%. 2 3 4 A review of the literature found few recent reports 5 6 showing a decrease in overall complications rates that may be due to advances in equipment, the evolution of techniques, and increased familiarity of the surgeons with arthroscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The complications evaluated were those seen with standard arthroscopy. The complication rates used for knee arthroscopy were derived from a recent article (2011) appearing in the Journal of Bone and Joint Surgery [34] (Table 2). The complication rates applied to the costs of shoulder arthroscopy were also derived from the literature [35,36] (Table 3).…”
Section: Methodsmentioning
confidence: 99%